Ocular Neuromyotonia: an update. (4th May 2021) - Raviskanthan, Subahari; Mortensen, Peter W; Lee, Andrew
ABSTRACT: Introduction : Ocular neuromyotonia (ONM) is a rare condition characterized by episodic involuntary extraocular muscle (EOM) contraction and spasm. ONM has many presumed causes of which radiation therapy and thyroid dysfunction are the most common. ONM symptoms can be mild, moderate, or severe and can be debilitating. This monograph reviews the current literature describing the clinical features, evaluation, and management of ONM. Areas covered: This pathogenesis, epidemiology, clinical presentation, diagnosis and differential diagnoses, workup, and treatment options of ocular neuromyotonia are discussed in detail. Expert opinion : ONM is a rare but highly distinctive disturbance of EOM that is typically associated with parasellar radiation therapy but can occur in other conditions such as thyroid eye disease. Neuroimaging studies are generally recommended but most cases develop in the setting of stable treated disease. Medical and surgical management of ONM is difficult with variable treatment response.